Back to school in the framework of COVID-19: a review for Latin America - Liliana Margarita Meza Cueto, Cristian Fernan Muñoz, Poma Ccora Deysi Melisa, Yeni Yauri Huiza, Molina-Azpeitia M. J., Marco Tulio Falconi Picardo (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review was carried out on the production and publication of research papers related to the study of the variable Back to School within the framework of COVID-19. The purpose of the bibliometric analysis proposed in this document is to know the main characteristics of the volume of publications registered in the Scopus database during the year 2020 and the first semester of 2021, achieving the identification of 80 publications in total. The information provided by this platform was organized by means of tables and figures, categorizing the information by Year of Publication, Country of Origin, Area of Knowledge and Type of Publication. Once these characteristics were described, the position of different authors regarding the proposed topic was referenced by means of a qualitative analysis. Among the main findings of this research, it is found that Brazil, with 46 publications, is the Latin American country with the highest production. The area of knowledge that made the greatest contribution to the construction of bibliographic material referring to the Back-to-School study within the framework of COVID-19 was social sciences with 21 published documents, and the type of publication that was most used during the abovementioned period was the journal article, which represents 83% of the total scientific production.